SOME COMMENTS CONCERNING UKRAINIAN POSTCOLONIAL STUDIES - YURCHUK, OLENA (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The paper focuses on the prospects offered by the postcolonial approach in the domain of Ukrainian literary studies. The study of the cultural legacy of the colonial past aimed at reinterpreting imperial and colonial discourses as well as their interaction and mutual influence responds to the crucial challenges facing the today’s Ukrainian society. The analysis of imperial and colonial discourses serves as a basis for identifying the author’s position, preserving the national essence, rethinking relations between the imperial center and periphery, overcoming infantile beliefs about the marginality of the colonized culture, and strengthening decentralization.
NIEKTÓRE UWAGI DOTYCZĄCE UKRAIŃSKICH STUDIÓW POSTKOLONIALNYCH
Keywords: postcolonial condition; postcolonial literature; postcolonial studies; imperial discourse